Geopolitical Pressures and Digital Sovereignity: Indonesia’s Strategic Response to US-China Data Hegemony - Herlanda, Mohammad Dzaky; Wirawan, Rendy (Jurnal Hubungan Internasional, 2025)
Data security has become a new arena of geopolitical competition amid global digital transformation, particularly between the United States and China. In this power struggle, developing countries such as Indonesia occupy a vulnerable yet strategic position. Using Indonesia as the main case study, this research analyzes the geopolitical dynamics of data through an analytical framework that integrates data geopolitics, technology dependency theory, and a hybrid hard-soft digital power approach. The study maps how China exerts digital influence through the expansion of digital ecosystems and infrastructure, while the United States does so through privacy concerns and international standards. Indonesia responds with multilateral digital diplomacy, national cyber infrastructure development, and legislation such as the Personal Data Protection (PDP) Law. Findings show that Indonesia seeks to preserve digital sovereignty through a digital non-alignment strategy, maintaining technological autonomy by avoiding excessive dependence on any major technological power bloc. This concept modernizes the historical Non- Aligned Movement in the context of today’s “digital Cold War” between the US liberal market model and China’s state-driven surveillance model. However, the strategy’s success depends on policy coherence, technological capacity, and global bargaining power. Overall, the study highlights both the strategic opportunities and structural challenges faced by developing states in achieving data sovereignty. Keywords: Geopolitics of Data, Digital Sovereignty, Cybersecurity, Digital Pressure.